2022
DOI: 10.1007/s40618-022-01830-6
|View full text |Cite
|
Sign up to set email alerts
|

Mean GH profile is more accurate than single fasting GH in the evaluation of acromegaly disease control during somatostatin receptor ligands therapy

Abstract: Purpose This study aims to compare the accuracy of mean GH profile (GHP) < 2.5 ng/ml and single fasting GH (SGH) < 1 ng/ml in the evaluation of disease control in acromegaly patients during somatostatin receptor ligands (SRLs) therapy. Methods We retrospectively enrolled 100 acromegaly patients, 68 responder, and 32 partial responder to SRLs. Controlled disease has been defined as IGF-I levels within age-related normal limits, while partial response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Similarly, Bona et al. ( 23 ) showed that the accuracy of the mean GH profile, associated with IGF-1, is higher than a single fasting GH measurement.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Bona et al. ( 23 ) showed that the accuracy of the mean GH profile, associated with IGF-1, is higher than a single fasting GH measurement.…”
Section: Discussionmentioning
confidence: 96%
“…Nadir GH was measured after a 75 g glucose tolerance test. In diabetic patients and/or those treated with somatostatin analogs (SSA), serum GH levels were determined every 30 min, and the arithmetical mean was counted based on five measurements [18,19,23,24]. All patients underwent an MRI scan (or CT, in case of contraindications) of the pituitary gland to determine image characteristics: tumor size, intratumor hemorrhage, and invasion type.…”
Section: Methodsmentioning
confidence: 99%
“…Nadir GH above 1 ng/mL in 75 g oral glucose tolerance test (patients without diabetes) or random GH levels above 2.5 ng/mL (mean of five measurements repeated every 30 min-in patients with diabetes) [18,19,23,24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical treatment can effectively lead to biochemical control. Furthermore, baseline characteristics that can impact long-term outcomes include age at diagnosis ( 7 ), gender ( 7 ), preoperative serum levels of GH and IGF-1 ( 8 - 13 ), preoperative medication ( 12 ), tumor size ( 8 , 9 , 12 ), invasiveness ( 12 , 14 ), Knosp grading scores ( 8 , 9 , 12 ), and histological pathology [Ki-67, somatostatin receptor subtype 2 expression, arylhydrocarbon receptor inter acting protein (AIP) expression, and granularity] ( 14 ). Therefore, identifying independent factors that predict long-term outcomes, such as biochemical remission or recurrence, may be crucial in facilitating clinical management.…”
Section: Introductionmentioning
confidence: 99%